2008
DOI: 10.1007/s00216-008-1987-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of methyl parathion hydrolase (MPH) as a labeling enzyme

Abstract: Methyl parathion hydrolase (MPH) is an enzyme that catalyzes the degradation of methyl parathion, generating a yellow product with specific absorption at 405 nm. The application of MPH as a new labeling enzyme was illustrated in this study. The key advantages of using MPH as a labeling enzyme are as follows: (1) unlike alkaline phosphatase (AP), horseradish peroxidase (HRP), and glucose oxidase (GOD), MPH is rarely found in animal cells, and it therefore produces less background noise; (2) its active form in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Another report stated that over 90% of maximum enzyme activity was retained between pH 7 and 9 and approximately 85% of the maximum activity can be maintained at both pH 6.86 and 9.18 [26], which is obviously different from the results in this manuscript. However Yang et al [35] reported that the optimal pH of MPH is 11.0. This discrepancy may be attributed to the different bioengineering methods used in enzyme preparation and the underlying reasons need further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Another report stated that over 90% of maximum enzyme activity was retained between pH 7 and 9 and approximately 85% of the maximum activity can be maintained at both pH 6.86 and 9.18 [26], which is obviously different from the results in this manuscript. However Yang et al [35] reported that the optimal pH of MPH is 11.0. This discrepancy may be attributed to the different bioengineering methods used in enzyme preparation and the underlying reasons need further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it is a monomer in solution and its 3D structure is known. Because of these features, MPH is recommended as a new analytical enzyme …”
Section: Introductionmentioning
confidence: 99%
“…fuscans. The methyl parathion hydrolase (MPH) protein is an enzyme that catalyzes the degradation of a wide range of organophosphate compounds, among them the methyl parathion, which is one of the most commonly used organophosphate fertilizers worldwide, especially in fruit and vegetable farming [54].…”
Section: Mutants Contributing To a Reduction In Hyperplasia And/or Nementioning
confidence: 99%